2011
DOI: 10.1089/acm.2010.0782
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Adding Whole-Body Vibration to Squat Training on the Functional Performance and Self-Report of Disease Status in Elderly Patients with Knee Osteoarthritis: A Randomized, Controlled Clinical Study

Abstract: Although the addition of whole-body vibration to squat training failed to result in a significant improvement in functional performance and self-reported status of knee osteoarthritis in the elderly, the intragroup results suggest that whole-body vibration may represent a feasible and effective way of improving the functionality and self-perception of disease status in older adults with knee OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
108
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(112 citation statements)
references
References 37 publications
3
108
1
Order By: Relevance
“…Though limited evidence is currently available regarding the effects of vibratory stimuli in individuals with knee pathologies, several positive outcomes have been reported, including decreases in pain and inflammation and improved self-reported function, strength, balance, and proprioception. [37][38][39][40][41][42][43][44][45] Our findings indicate that WBV and LMV may also reduce quadriceps AMI, potentially supporting a paradigm shift in the treatment of knee pathologies by suggesting that AMI should be minimized before attempting to strengthen the quadriceps. These findings imply that WBV and LMV may be useful adjuncts to current techniques for rehabilitation of knee pathologies which incur quadriceps AMI.…”
Section: Discussionmentioning
confidence: 59%
“…Though limited evidence is currently available regarding the effects of vibratory stimuli in individuals with knee pathologies, several positive outcomes have been reported, including decreases in pain and inflammation and improved self-reported function, strength, balance, and proprioception. [37][38][39][40][41][42][43][44][45] Our findings indicate that WBV and LMV may also reduce quadriceps AMI, potentially supporting a paradigm shift in the treatment of knee pathologies by suggesting that AMI should be minimized before attempting to strengthen the quadriceps. These findings imply that WBV and LMV may be useful adjuncts to current techniques for rehabilitation of knee pathologies which incur quadriceps AMI.…”
Section: Discussionmentioning
confidence: 59%
“…Improvements were noted in muscular power for the stable-platform vibration training group (WMD, 7.6 Newton-meters [Nm]; 95% CI, 3.5–11.6) versus the control group (isokinetic knee extension) (isometric peak torque knee extension, 11.9 Nm; 95% CI, 1.9–22.0) and in proprioception (ability to sense position and movement of the body) (WMD, −0.59 sec; 95% CI, −1.13 to 0.05) for the balance board vibration training versus control. In a more recent RCT of whole body vibration, Avelar et al 54 evaluated vibration training with squat training compared with squat training alone on functional performance and self-report of disease in older adults (n = 23) with knee OA. No significant differences were noted in functional performance (Berg Balance Scale score, timed get-up-and-go test, chair stand test, 6-minute walk test) or WOMAC scores between the groups in this small study, but both exercise groups showed improvement in these outcomes compared with their baseline status (eg, 6-minute walk test pre-vibration training, 424 m vs 448 m after training, P < 0.05; pre-squat training, 394 sec vs 421 sec post-training, P < 0.05).…”
Section: Methodsmentioning
confidence: 99%
“…WBV provides amplitude of displacement (ranging from 0.7 to 14 mm) and a mechanical oscillation of a specific frequency (ranging from 0.5 to 80 Hz) [15,16]. Several studies have demonstrated that whole body vibration exercise can reduce pain for women with fibromyalgia syndrome [17], young patients with musculoskeletal pain [18], and elderly patients with knee osteoarthritis [19]. …”
Section: Introductionmentioning
confidence: 99%